Benefits of Arthroscopy in Osteoarthritis of the Knee - Thamyongkit, MD, Sorawut; Yuktanandana, MD, Pongsak (Journal of Southeast Asian Orthopaedics, 2022)
As the life span of the world’s population continues to rise, the prevalence of osteoarthritis (OA) is also expected to increase. The goals of treatment are to reduce symptoms and slow the progression of the disease. Numerous treatment strategies are used for osteoarthritis of the knee including non-operative and operative procedures. Arthroscopic surgery has been used for many procedures in knee osteoarthritis with the advantage of only a small incision for many procedures. However, recent studies show that arthroscopy in knee OA patients has limited benefit and is not recommended as a routine treatment. Patients with acute onset of pain and effusion, loose bodies or large meniscal tears could get better results. Therefore, proper evaluation and management of osteoarthritis of the knee are key factors.